Phage Therapy as Adjuvant to Conservative Surgery and Antibiotics to Salvage Patients With Relapsing S. aureus Prosthetic Knee Infection - Ferry, Tristan; Kolenda, Camille; Batailler, Cécile; Gustave, Claude-Alexandre; Lustig, Sébastien; Malatray, Matthieu; Fevre, Cindy; Josse, Jérôme; Petitjean, Charlotte; Chidiac, Christian; Leboucher, Gilles; Laurent, Frédéric (Frontiers in Medicine, 2020)
Objectives: To report the management of 3 consecutive patients with relapsing S. aureus prosthetic knee infection (PKI) for whom explantation was not feasible who received a phage therapy during a ‘Debridement Antibiotics and Implant retention’ (DAIR) procedure followed by suppressive antimicrobial therapy. Methods: Each case was discussed individually in our reference center and with the French National Agency (ANSM). The lytic activity of 3 phages targeting S. aureus, that was produced with a controlled and reproducible process, was assessed before surgery (phagogram). Hospital pharmacist assembled extemporaneously the phage cocktail (1 ml of 1x1010 PFU/ml for each phage) as “magistral” preparation (final dilution 1x109 PFU/mL), that was administered by the surgeon directly into the joint, after the DAIR procedure and joint closure (PhagoDAIR procedure). Results: Three elderly patients were treated with the PhagoDAIR procedure. Phagograms revealed a high susceptibility to at least 2 of the 3 phages. During surgery, all patients had poor local conditions including pus in contact to the implant. After a prolonged follow-up, mild discharge of synovial fluid persisted in 2 patients, for whom a subsequent DAIR was performed showing only mild synovial inflammation without bacterial persistence or super-infection. The outcome was finally favorable with a significant and impressive clinical improvement of the function. Conclusions: The PhagoDAIR procedure has the potential to be used as salvage for patients with relapsing S. aureus PKI, in combination with suppressive antibiotics to avoid considerable loss of function. This report provides preliminary data supporting the set-up of a prospective multicentric clinical trial.